THE LOTTTERY, KARYASIDRLEY JACKSON: KAJIAN DEKONSTRUKTIF - Syam, Essy (Jurnal Ilmu Budaya, 2015)
This writing deals with an analysis of a literary work entitles "The Lottery" written by Shirley Jackson. In this case, the work is analyzed deconstructively. The result shows that there are some events found which undermine the stable, universal meanings such as the concept of lottery itself which is signified very differently from the stable meaning. Besides, the pleasant atmosphere presented at the beginning of the work doesn't offer enjoyable events that follow, what makes it more astonishing is the fact that the villagers sacrifice one of them only because they get used to it and evenworse, they enjoy to sacrife one of them.